Sediment contamination and toxicity of Marine Protected Areas in southeastern Brazilian coast: A baseline for management planning - Moreira, Lucas Buruaem [UNESP]; Fernandes, Gabrielle Melo; Figueira, Rubens Cesar Lopes; do Nascimento, Ronaldo Ferreira; Cavalcante, Rivelino Martins; Machado, Wilson Thadeu Valle; de Souza Abessa, Denis Moledo [UNESP] (Elsevier, 2021)
Recent studies have shown that the effectiveness of establishing Marine Protected Areas (MPAs) is threatened by toxic effects of contaminants. São Paulo is the most economically developed state of Brazil, and its coast is protected by a system of MPAs, including the North Shore Marine Protected Area (NSMPA). The present study provides a first assessment of sediment quality in NSMPA and two reference sites. Concentrations of arsenic (As), metals (Al, Fe, Cd, Cr, Cu, Ni, Pb, and Zn) and polycyclic aromatic hydrocarbons (PAHs) and its sources were determined. Comparisons with sediment quality guidelines indicated low contamination, as confirmed by the Geoaccumulation Index, which classified the results as background levels. Whole-sediment exposures of the amphipod Tiburonella viscana were performed to estimate possible acute effects, but samples exhibited no toxicity. The results presented in this study represent a baseline for further monitoring programs of MPAs, supporting conservation actions of management plans.
Keywords: Amphipods; Background values; Geochemistry; Marine conservation; Metals; Polycyclic aromatic hydrocarbons